Experiencing other minds in the courtroom - Feigenson, Neal (Chicago : The University of Chicago Press, 2017)
In 'Experiencing Other Minds in the Courtroom', Neal Feigenson turns the courtroom into a forum for exploring the profound philosophical, psychological and legal ramifications of our efforts to know what other people's conscious experiences are truly like. Drawing on disciplines ranging from cognitive psychology to psychophysics to media studies, Feigenson harnesses real examples of digitally simulated subjective perceptions to explain how the epistemological value of this evidence is affected by who creates it, how it is made, and how it is presented.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 17, 2017).
Keywords: Evidence (Law); Judicial process; Examination of witnesses; Law; Jurisprudence & general issues; Law & society, sociology of law; Laws of specific jurisdictions & specific areas of law; Legal systems: courts & procedure